News online and public opinion: how Malaysians responded to news on a state by-election - Mohamed, Shafizan; Idid, Syed Arabi; Abdul Manan, Kamaruzzaman (2019)
This presentation discusses whether news online such as Facebook set the agenda for its readers. In response to the importance of social networking sites as sources of information, news media organizations have set up Facebook channels in which they publish news stories or links to articles. This allows for a wider news reach as well as audience participation. When audience members read and subsequently comment on news articles on Facebook, it becomes possible to identify public opinions and sentiments on the issues being covered.